Detecting deletions in the critical region for lissencephaly on 17p13.3 using fluorescent in situ hybridisation and a PCR assay identifying a dinucleotide repeat polymorphism. Issue 4 (April 1995) - Pilz, D T; Dalton, A; Long, A; Jaspan, T; Maltby, E L; Quarrell, O W
Abstract : During a study of lissencephaly in England and Wales, 23 children were identified with this diagnosis. They were classified as follows: three children had Miller-Dieker syndrome (MDS), 13 had isolated lissencephaly sequence (ILS), two had type II lissencephaly, and five children were reclassified as focal or diffuse cortical dysplasia. Microdeletions of chromosome 17p13.3, also known as the Miller-Dieker critical region, have been associated with both MDS and ILS. We used the commercially available Oncor probe for fluorescent in situ hybridisation (FISH) studies on 14 patients and a further four were studied elsewhere. Deletions were identified in all three MDS patients and two of the ILS patients. These results are consistent with previously reported data. No deletions were found in those patients with focal or diffuse cortical dysplasia. In addition, a CA repeat polymorphism which maps to the Miller-Dieker critical region was studied in 12 families and was informative in nine; the results were consistent with the FISH data. We conclude that FISH is a reliable method to detect deletions in patients with MDS and ILS and also useful to identify chromosome rearrangements in their parents which are not detected by conventional cytogenetic analysis. The PCR assay, if informative, is also reliable and a useful alternative if only DNA is available. None of the five children with atypical radiological features had a deletion. We therefore suggest that as well as looking for other aetiologies a careful review of the diagnosis should be made of the MDS or ILS cases in whom a deletion is not found.